2019
DOI: 10.1371/journal.pone.0213949
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the insecticide-treated bednet PermaNet 2.0 reduces the longevity of the wild African malaria vector Anopheles funestus but GSTe2-resistant mosquitoes live longer

Abstract: BackgroundDespite the increased report of insecticide resistance in malaria vectors, its impact on mosquito’s life-traits after exposure to insecticide-treated nets remains under investigated. Here, we assessed the effects of exposure to PermaNet 2.0 on several life traits of An. gambiae s.l. and An. funestus s.l. field mosquitoes in Cameroon.MethodologyFemale Anopheles mosquitoes were collected indoor using electric aspirators in southern Cameroon (Obout) in 2016. After assessing the resistance status of F1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
(43 reference statements)
8
23
0
Order By: Relevance
“…The multiple insecticide resistance patterns observed in the An. funestus s.s. population to pyrethroids and DDT in Elende corresponds to the trends observed in Gounougou (2012) [9] and higher than in Obout (2016) [44] but lower than in Tibati (2018) [34]. Moreover, the high resistance pattern of An.…”
Section: Multiple and High Insecticide Resistance In Both Major Vectosupporting
confidence: 68%
See 1 more Smart Citation
“…The multiple insecticide resistance patterns observed in the An. funestus s.s. population to pyrethroids and DDT in Elende corresponds to the trends observed in Gounougou (2012) [9] and higher than in Obout (2016) [44] but lower than in Tibati (2018) [34]. Moreover, the high resistance pattern of An.…”
Section: Multiple and High Insecticide Resistance In Both Major Vectosupporting
confidence: 68%
“…However, this result is similar to mortality rate recorded in An. funestus s.s. from Obout that exhibited very high level of resistance to dieldrin (4.35% mortality rate) [44]. This high frequency could be as a result of strong resistance selection due to environmental persistence of insecticide residues since its withdrawal from public and agricultural use in Cameroon.…”
Section: Elevated Metabolic Resistance In An Funestus Differs With Hmentioning
confidence: 99%
“…Females that were exposed to deltamethrin fed less than females that were not exposed. Our findings were consistent with Glunt et al, [26] and contrary to what was observed by Tchakounte et al, [27] who showed that exposure of mosquitoes to PermaNet 2.0 deltamethrintreated bednet presented no effect of on their blood feeding ability. From an epidemiological point of view, our findings can be translated into a reduction in transmission as the drop in the rate of mosquito bites also means less risk of infection with plasmodium.…”
Section: Discussionsupporting
confidence: 93%
“…PermaNet® 2.0 has been among the most widely distributed LLIN brand in the recent decade and bioefficacy studies have been conducted in several countries. Most of these studies used LLINs dating back to 2012 and before, and showed very good bioefficacy of PermaNet® 2.0 [25][26][27][28][29]. In tests conducted in an African setting (Northern Tanzania), PermaNet® 2.0 from 2017 were reported to fulfil all requirements [30].…”
Section: Discussionmentioning
confidence: 99%